HUBUNGAN KOMPETENSI DAN MOTIVASI KERJA DENGAN KINERJA TENAGA ADMINISTRASI SEKOLAH - Rossa Valentina; Maisyaroh Maisyaroh; Desi Eri Kusumaningrum (Universitas Negeri Malang, 2018)
Abstract: The research is done to describe the level of competency of school administrative staff, describe the level of work motivation of school administrative staff, describe the level of performance of school administrative staff, and understand the connection of competency and work motivation with the performance of the school administrative staff. The approach of this study is quantitative that is correlation descriptive research with 111 respondents. As forcollecting data is questionnaire. The results of the research show that the competency of school administrative staff is high, the work motivation of school administrative staff is high, the performance of school administrative staff is high, and there is a relationship of competency and work motivation with performance of school administrative staff. Keywords: competency, work motivation, performance Abstrak: Tujuan penelitian ini untuk mendeskripsikan tingkat kompetensi tenaga administrasi sekolah, mendeskripsikan tingkat motivasi kerja tenaga administrasi sekolah, mendeskripsikan tingkat kinerja tenaga administrasi sekolah, serta mengetahui hubungan kompetensi dan motivasi kerja dengan kinerja tenaga administrasi sekolah. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan deskriptif korelasional, dengan 111 orang responden. Hasil penelitian menunjukkan bahwa kompetensi tenaga administrasi sekolah tergolong tinggi, motivasi kerja tenaga administrasi sekolah tergolong tinggi, kinerja tenaga administrasi sekolah tergolong tinggi, dan terdapat hubungan kompetensi dan motivasi kerja dengan kinerja tenaga administrasi sekolah. Kata Kunci: kompetensi, motivasi kerja, kinerja